The Use of Alum and Polyelectrolyte Coagulants as Admixtures in Concrete Bunkers Production - Hama, Ako Rashed (Sulaimani Journal for Engineering Sciences, 2019)
This study estimates and determines the possibility of using water treatment plant sludge as a kind of chemically enriched water cement ratio in preparing high strength concrete bunkers which are one of the most important protection barriers that soldiers usually need them and use them during wars, and gun fighting to protect themselves from bullet attacks.In this paper, two main different chemicals have been used as a concrete additives which are mainly those used in coagulation processes in water treatment plants and those two conventional chemicals were alum and polyelectrolyte which are usually have been used as a coagulants and coagulant aids in Dokan water treatment plant (70Km south west of Sulaimani city, Iraq) and they lead to produce a coagulant’s sludge waste which settled at the end of sedimentation process on the bottom of the clarifier tanks. Samples of the raw water from the inlets have been tested for a continuous period of 12months including the heavy rainy days, summer and winter seasons especially in the beginning of the stratification periods of Dokan Lake the source of the treatment plant. The tests included jar tests and turbidity of the samples, then the finding the optimum quantity of the two coagulants alum and polyelectrolytes. The records of the performed tests showed that the maximum rate of the used alum was 15mg/L while the maximum used amount of polyelectrolyte was 10mg/L. Those two maximum high values of rates of alum and polyelectrolytes and their hybrid mixing rates have been used in preparation 7concrete prototype bunkers of dimensions 80cm x 80cm x 15cm with an admixture rates of 15mg/L alum, 15mg/L polyelectrolyte, 10mg/L alum, 10mg/L polyelectrolyte , 10mg/L alum with 5 mg/L polyelectrolyte, 5 mg/L alum with 5 mg/L polyelectrolyte and zero mg/L for both of them (blank). Two different types of tests have been performed for the prepared concrete bunkers; the first one was in-lab compression tests for the cube samples of the prototypes concrete inside the laboratory and the second one was outdoor field shouting tests for the prepared concrete bunker prototypes using 12.7 mm gun fire bullets and a shooting from a distance of 100m targeting. Concrete compression laboratory tests have been conducted for 7,21and 28days aged concrete prototype bunkers while the depth, length and the diameter of the cracks and punching of the bullet hitting locations on the targeted prototype concrete bunker were measured. The results of this research reveals that adding alum along either in 15mg/l or 10 mg/ l doses in the three aged concrete 7,21,and 28 days will affect inversly on the concrete compaction strength by a (1% – 8%) while adding the other mensioned doses (polyelectrolyte along with different doses 10mg/l or 15 mg/l and a hybird doses of alum 10mg/l mixed with polyelectrolite 10mg/l ,will help in increasing the concrete compression strength of the concrete by 3.5% to 12%. Through out the tests its clearly appeared that the optimum coagulant in increasing the capacity of the concrete is polyelectrolyte and with a dosage of 15mg/l and it helps to increase the capacity of the concrete to 9% at 7days , 11.5 % at 21days and 13% at 28days from the age of the concrete .The results showed that the penetration depth for all the seven concrete bunker prototypes, evaluates each prototype performance via their penetration depths, because the penetration depth of the bullet is the most important variable in selecting the best performance concrete bunker prototype among all of them. The results also showed that the minimum penetration was 1.7cm of polyelectrolyte used coagulant prototype of 15mg/L, and the maximum ratio about 2.2cm. The maximum destroyed diameter during the field bullet shooting test resulting that the highest value of maximum destroyed diameter was 20cm with polyelectrolyte used coagulant prototype of 10 mg/L and the lowest one was 10cm while using polyelectrolyte coagulant as admixture of 15 mg/l dosage.
Keywords: Alum; Polyelectrolyte; Coagulants; waterworks Sludge; Concrete Bunkers; recycle